Resilience and Work Stress in Teachers - Nurmalitasari, Femmi; Hanurawan, Fattah (Jurnal Sains Psikologi, 2023)
This study aims to determine whether there is a relationship between resilience and work stress in teachers at SMA Negeri 2 Lumajang. The research design used in this study is descriptive correlational. The respondents of this study were 55 teachers who taught at SMA Negeri 2 Lumajang. The sampling technique is purposive sampling. The research instrument used is the resilience scale and work stress scale. The resilience scale consists of 39 items with reliability of 0.957, and the work stress scale consists of 57 items with reliability of 0.977. Research data were analyzed using descriptive techniques and Pearson product-moment correlation analysis. The results showed a negative and significant relationship between resilience and work stress for teachers at SMA Negeri 2 Lumajang (rxy equal to -0.654; p equal to 0.000 less than 0.05). This result can be interpreted that if the resilience is high, the work stress is low, and vice versa; if the resilience is low, the work stress is high.